Online learning challenges postgraduate certificate in education History students faced during COVID-19 at the University of Zululand (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This paper intends to share empirical challenges of Postgraduate Certificate in Education (PGCE) History students faced during COVID-19. COVID-19 was characterised by, amongst other things, social distancing, which put lectures on hold in favour of online learning. A group of 32 students participated in the study. Data were collected through narrative inquiry, and a thematic data analysis method was used. The study revealed that PGCE history students faced challenges of adapting to and accessing online learning and library materials, an expectation to do a lot of academic work, individual instead of classroom or library learning, unconducive home learning space, lack of parental support, and financial constraints. Therefore, this study concludes that students struggled to cope with online learning and recommends that institutions of higher learning should consider the above challenges when undertaking online learning under COVID-19 conditions in future.
Keywords: Online learning; Challenges; PGCE History students; COVID-19; Lectures; Teaching